Sumoylation regulates nuclear localization of lipin-1alpha in neuronal cells. - Guang-Hui Liu; Larry Gerace (PLoS ONE)
Lipin-1 is a protein that has dual functions as a phosphatidic acid phosphohydrolase (PAP) and a nuclear transcriptional coactivator. It remains unknown how the nuclear localization and coactivator functions of lipin-1 are regulated. Here, we show that lipin-1 (including both the alpha and beta isoforms) is modified by sumoylation at two consensus sumoylation sites. We are unable to detect sumoylation of the related proteins lipin-2 and lipin-3. Lipin-1 is sumoylated at relatively high levels in brain, where lipin-1alpha is the predominant form. In cultured embryonic cortical neurons and SH-SY5Y neuronal cells, ectopically expressed lipin-1alpha is localized in both the nucleus and the cytoplasm, and the nuclear localization is abrogated by mutating the consensus sumyolation motifs. The sumoylation site mutant of lipin-1alpha loses the capacity to coactivate the transcriptional (co-) activators PGC-1alpha and MEF2, consistent with its nuclear exclusion. Thus, these results show that sumoylation facilitates the nuclear localization and transcriptional coactivator behavior of lipin-1alpha that we observe in cultured neuronal cells, and suggest that lipin-1alpha may act as a sumoylation-regulated transcriptional coactivator in brain.